2018
DOI: 10.1159/000489315
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study Evaluating the Performance of LENT Score in the Selected Population of Malignant Pleural Effusion from Lung Adenocarcinoma in Singapore

Abstract: Background: Patients with malignant pleural effusion (MPE) secondary to lung cancer have been associated with poor prognosis historically. LENT score developed to risk-stratify unselected patients with MPE predicts prognosis of < 6 months in patients with lung cancer. Objective: To assess the performance of LENT score in predicting prognosis in selected population of MPE secondary to lung adenocarcinoma alone. Methods: A retrospective observational study was conducted by reviewing the medical records of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 17 publications
3
32
1
2
Order By: Relevance
“…The LENT score system was calculated by four variables, including pleural fluid lactate dehydrogenase (LDH) level, ECOG PS, neutrophil‐to‐lymphocyte ratio (NLR), and tumor type, and it is widely used in risk stratification of MPE patients. However, a recent study suggested that it underestimates the prognosis in patients with MPE caused by lung adenocarcinoma . The recently published PROMISE score system includes a clinical score method and a biological score method, which is a clinical score plus tissue inhibitor of metalloproteinases 1 (TIMP1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LENT score system was calculated by four variables, including pleural fluid lactate dehydrogenase (LDH) level, ECOG PS, neutrophil‐to‐lymphocyte ratio (NLR), and tumor type, and it is widely used in risk stratification of MPE patients. However, a recent study suggested that it underestimates the prognosis in patients with MPE caused by lung adenocarcinoma . The recently published PROMISE score system includes a clinical score method and a biological score method, which is a clinical score plus tissue inhibitor of metalloproteinases 1 (TIMP1).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study suggested that it underestimates the prognosis in patients with MPE caused by lung adenocarcinoma. 20 The recently published PROMISE score system 21 includes a clinical score method and a biological score method, which is a clinical score plus tissue inhibitor of metalloproteinases 1 (TIMP1). However, this system can only predict the 3-month mortality, and adding TIMP1 to the score system only contributed very modest effects, which limited its clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…In the present issue of Respiration, Abisheganaden et al [12] reports the application of the LENT score in a selected population of patients with MPE secondary to lung adenocarcinoma in Singapore. The key finding is that the LENT score considerably underestimated the prognosis for the selected patients with MPE and therefore needed modification in order to be applicable.…”
mentioning
confidence: 99%
“…The prevalence of EGFR mutations in Abisheganaden's population was 55.7%, and all patients with EGFR mutations also received TKI treatment [12]. The population of patients from which the LENT score was derived consisted of a UK, Dutch, and Australian cohort, where the prevalence of EGFR mutations was estimated between 12 and 15% [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation